Effective strategies to motivate nursing home residents in oral care and to prevent or reduce responsive behaviors to oral care: A systematic review. - Matthias Hoben; Angelle Kent; Nadia Kobagi; Kha Tu Huynh; Alix Clarke; Minn N Yoon (PLoS ONE)
Background Poor oral health has been a persistent problem in nursing home residents for decades, with severe consequences for residents and the health care system. Two major barriers to providing appropriate oral care are residents' responsive behaviors to oral care and residents' lack of ability or motivation to perform oral care on their own. Objectives To evaluate the effectiveness of strategies that nursing home care providers can apply to either prevent/overcome residents' responsive behaviors to oral care, or enable/motivate residents to perform their own oral care. Materials and methods We searched the databases Medline, EMBASE, Evidence Based Reviews-Cochrane Central Register of Controlled Trials, CINAHL, and Web of Science for intervention studies assessing the effectiveness of eligible strategies. Two reviewers independently (a) screened titles, abstracts and retrieved full-texts; (b) searched key journal contents, key author publications, and reference lists of all included studies; and (c) assessed methodological quality of included studies. Discrepancies at any stage were resolved by consensus. We conducted a narrative synthesis of study results. Results We included three one-group pre-test, post-test studies, and one cross-sectional study. Methodological quality was low (n = 3) and low moderate (n = 1). Two studies assessed strategies to enable/motivate nursing home residents to perform their own oral care, and to studies assessed strategies to prevent or overcome responsive behaviors to oral care. All studies reported improvements of at least some of the outcomes measured, but interpretation is limited due to methodological problems. Conclusions Potentially promising strategies are available that nursing home care providers can apply to prevent/overcome residents' responsive behaviors to oral care or to enable/motivate residents to perform their own oral care. However, studies assessing these strategies have a high risk for bias. To overcome oral health problems in nursing homes, care providers will need practical strategies whose effectiveness was assessed in robust studies.